2011
DOI: 10.1016/j.sjbs.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Protection of human erythrocyte using Crinum asiaticum extract and lycorine from oxidative damage induced by 2-amidinopropane

Abstract: The intention of this investigation was to evaluate the free radical scavenging activity and erythrocyte protective activity of ethanolic extract of Crinum asiaticum (L) and lycorine. The ethanolic extract of C. asiaticum (L) and lycorine were found to have different levels of antioxidant properties in the test models. Both ethanolic extract of C. asiaticum (L) (0.5-2.5 mg/ml) and lycorine (0.010 mg-0.050 mg/ml) increases the percentage of lipid peroxidation inhibition (26.25 ± 0.23% and 19.25 ± 0.23%) and enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
(25 reference statements)
1
19
0
Order By: Relevance
“…To best understand the biological potential of the G. ulmifolia extracts, we used human blood cells subjected to oxidative stress induced by different oxidant agents. Initially, we used AAPH, a water-soluble azo compound that decomposes at 37°C generating peroxyl radicals (ROO) [ 49 ] responsible for oxidizing erythrocyte membrane lipids and proteins [ 50 ]. Azo compound-derived ROO and those formed physiologically and pathologically in vivo react with biomolecules similarly, facilitating the study of the oxidation kinetics of biological molecules and their possible protection [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…To best understand the biological potential of the G. ulmifolia extracts, we used human blood cells subjected to oxidative stress induced by different oxidant agents. Initially, we used AAPH, a water-soluble azo compound that decomposes at 37°C generating peroxyl radicals (ROO) [ 49 ] responsible for oxidizing erythrocyte membrane lipids and proteins [ 50 ]. Azo compound-derived ROO and those formed physiologically and pathologically in vivo react with biomolecules similarly, facilitating the study of the oxidation kinetics of biological molecules and their possible protection [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lycorine showed significant DPPH scavenging effects [64]. It also exerted protective effects on human erythrocytes against oxidative damage induced by 2-amidinopropane due to its antioxidant nature [65]. Lately, lycorine has been shown to exhibit significant hepatoprotective effects against CCl 4 -induced oxidative stress in Swiss albino mice at 5 mg/kg that were also comparable to Silymarin.…”
Section: Antioxidant Hepatoprotective and Metabolic Effectsmentioning
confidence: 99%
“…Similarly, 92 , Ilavenil et al showed that C. asiaticum L. ethanolic extract and lycorine possess human erythrocyte protective effects against oxidative damage induced by 2-amidinopropane. The effects were attributed to their antioxidant nature.…”
Section: Antioxidant Hepatoprotective and Metabolic Effectsmentioning
confidence: 94%